2004
DOI: 10.1038/sj.bjp.0705771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclooxygenase inhibitor pretreatment on nitric oxide production, nNOS and iNOS expression in rat cerebellum

Abstract: British Journal of Pharmacology (2004) 141, 1234. doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Sawynok and Reid [2012] demonstrated an involvement of spinal adenosine A 1 and CB 1 cannabinoid receptors in antinociception by acetaminophen. Girolamo et al, 2003], and regulates brain opioid receptors [Orti et al, 1999]. In this study, we observed that systemic administration of naloxone reduced the antinociceptive effects of the combination, suggesting the participation of opioid pathways in the mechanisms of action of the acetaminophen-lysine clonixinate combination.…”
Section: Discussionmentioning
confidence: 50%
“…Sawynok and Reid [2012] demonstrated an involvement of spinal adenosine A 1 and CB 1 cannabinoid receptors in antinociception by acetaminophen. Girolamo et al, 2003], and regulates brain opioid receptors [Orti et al, 1999]. In this study, we observed that systemic administration of naloxone reduced the antinociceptive effects of the combination, suggesting the participation of opioid pathways in the mechanisms of action of the acetaminophen-lysine clonixinate combination.…”
Section: Discussionmentioning
confidence: 50%
“…First, pretreatment with COX inhibitors inhibited the augmented expression of iNOS and nNOS in rat hippocampal slices treated with LPS [26]. Second, like iNOS and nNOS deficient mice, neurons in substantia nigra of COX-2 deficient mice are less prone to MPTP induced cytotoxicity than wild type mice [32].…”
Section: No and Cgmp In Neurodegenerative Diseasesmentioning
confidence: 98%
“…Consequently, the production of cytokines secreted by macrophages at the injury site is hampered, reducing the inflammatory response (Rainsford, 2009). Furthermore, researchers have shown that ibuprofen reduces the activity of inducible isoform of nitric oxide synthase, which produces changes in transmembrane ion flux (Liles & Flecknell, 1992) and is also involved in inflammatory processes (Di Girolamo et al, 2003). Interestingly, a study described by Da Silva et al (2011) revealed that athletes who participated in the anti-doping control of the XV Pan-American Games reported a high intake of NSAIDs during competition when compared with out-of-competition athletes.…”
mentioning
confidence: 99%